Are Plurilaterals a promising trade liberalization modality? - Bouët, Antoine; Laborde Debucquet, David (Instituto Interamericano de Cooperación para la Agricultura, 2021)
After 50 years of success, multilateral trade liberalization, conducted under the umbrella of the World Trade Organization (WTO), is in a deadlock, as illustrated by the impasse in which the Doha Round is for almost 20 years. Many explanations have been advanced. Let us quote three of them. First, there are many trading partners involved in the negotiation and their interests are too heterogeneous, such that there is no outcome benefiting all parties (Bouët and Laborde, 2010). Second the welfare gains expected from a new round of multilateral trade liberalization are small compared to the internal redistributive effects that it may imply (Rodrik, 1994). Third, there is asymmetric information not only between policymakers and the producers they want to protect from income variation, but also between trade negotiators at WTO about the political influence of domestic producers in each country. This double informational asymmetry gives birth to informational rents and makes difficult the implementation of free trade (Bouët, Laborde and Martimort, 2020).